Hidradenitis Suppurativa: Current Understanding of Pathogenic Mechanisms and Suggestion for Treatment Algorithm - Seyed Jafari, S. Morteza; Hunger, Robert E.; Schlapbach, Christoph (Frontiers in Medicine, 2020)
Hidradenitis suppurativa is one of the most distressing dermatological conditions and has a significant negative impact on patients' quality of life. However, the exact pathogenic mechanisms remain incompletely understood and—therefore—efficient therapies are still lacking. The current manuscript focuses on new findings on its pathogenic mechanisms and aims to provide practical therapy recommendations.